Transactional sex and age-disparate sexual partnerships among adolescent girls and young women in Tanzania - Rucinski, Katherine B.; Mbita, Gaspar; Atkins, Kaitlyn; Majani, Esther; Komba, Albert; Casalini, Caterina; Drake, Mary; Makyao, Neema; Galishi, Anthony; Mlawa, Yeronimo; Wamoyi, Joyce; Schwartz, Sheree; et al. (Frontiers in Reproductive Health, 2024)
Adolescent girls and young women (AGYW) continue to experience a high incidence of HIV in southern and eastern Africa, even in the context of large-scale HIV prevention interventions. In Tanzania, AGYW account for the largest proportion of new infections and have a higher risk of HIV acquisition than males of comparable age. We used routinely collected data from the PEPFAR/USAID-funded Sauti Project, a large combination HIV prevention program, to examine the relationship between transactional sex and sex with older partners among AGYW in Tanzania (2015-2020). Out-of-school AGYW 15-24 years completed a vulnerability index and were tested for HIV. We estimated weighted prevalence ratios (PR) and 95% confidence intervals (CI) for the associations of transactional sex (sex exchanged for money/services/gifts outside of sex work) and sex with older partners (≥5-years older, ≥10-years older) with prevalent HIV. Age cutoffs of 5 and 10 years were used to align partner age differences with age-disparate and intergenerational sex, respectively. We assessed potential synergism between exposures, and subgroup analyses explored associations among girls 15-19. 67,357 AGYW completed the vulnerability index and 14,873 had captured HIV testing records. Median age was 20 years (IQR 18-22). Transactional sex and age-disparate sex were common (35% and 28%, respectively); 13% of AGYW reported both behaviors. HIV prevalence was associated with both transactional sex (PR:1.28; 95% CI 1.00-1.63) and age-disparate sex (PR:1.26, 95% CI 0.99-1.60). In common referent analysis, transactional sex remained strongly associated with HIV, even in the absence of age-disparate sex (PR 1.41; 95% CI 1.02-1.94). Evidence of statistical synergism was not present, suggesting both transactional sex and age-disparate sex operate through similar pathways to increase HIV risk. Increased specificity within HIV prevention programs is needed to better meet the sexual and reproductive health needs of AGYW at high risk of HIV in Tanzania, including investment in tailored youth-friendly strategies for AGYW who have been marginalized from the current HIV response.